The Construction of National Legal Systems from Pancasila's Perspective - Yuliartini, Ni Putu Rai; Putra, Ida Bagus Wyasa; Atmaja, Gede Marhendra Wija; Mangku, Dewa Gede Sudika (Universitas Negeri Malang, 2022)
This study aimed to analyze Pancasila as the source of all sources of law and the actualization of Pancasila in constructing the national legal system. The type of research was normative legal research with a statutory and conceptual approach. The researchers did library research techniques as secondary data sources. This study analyzed qualitatively juridically. The study results showed that the formulation of laws in every political stage of legal reform should follow the values contained in Pancasila as the source of all sources of law. The formation or renewal of norms would have implications for interests and impact people's lives or the construction of national and community life. In the development of law, Pancasila was a philosophical foundation, namely the view of life, awareness, and legal ideals of the Indonesian nation. The values of divinity, humanity, unity, democracy, and justice should be actualized into the legal substance, legal structure, and legal culture that would be built.